A study on customers' perception towards service quality at the main counter of Amanah Saham Nasional Berhad, Kuala Lumpur / Azlina Abdul Ghani - Abdul Ghani, Azlina (Faculty of Business and Management, 2006)
This thesis present a study, which has sought to take steps towards increasing both knowledge of how customers' perceived the service quality delivered by the main counter of ASNB and at the same time identifies the difference of their perceptions towards the main counter of ASNB service quality based on their demographic backgrounds. Main counter is a place where people come and do many and different types of transactions, so it is vital not only in establishing, show credibility and confidence towards its customers to trust ASNB to handle their investment and unit trust. It is noteworthy to investigate how customers perceive the service quality of the main counter in order for ASNB to take up competitive position upon their ability to deliver quality services to the customers throughout Malaysia. This quantitative study has adopted an application of Prasuraman, Zeithml, Berry and Groonroos's SERVQUAL questionnaire to sample customers that come to the main counter of ASNB to do their transaction. A survey was conducted through distribution of questionnaires to the customers from different background profile. A total of 110 respondent self administered questionnaire were distributes and collected simultaneously, which have resulted a 100% response rate. However 100 useable questionnaires were analyzed. Using quantitative analyzes, the data was computed by using SPSS program and analyzed based on the perception minus expectation gap adopted from SERVQUAL model.